Onboard, tethered IL-12 boosts potency of the Tmod NOT gate and preserves selectivity - Alexander Kamb; Sara Imboden; Dongwoo Lee; Mark E Daris; Alexandre Zampieri; Jingli A Zhang; Sanam Shafaattalab; Jushen Liang; Richele Bruno; Jon Torres; Alexander Partin; Timothy P Riley (Journal for ImmunoTherapy of Cancer)
Background To reach their full potential in cancer therapy, immune cells engineered with synthetic constructs must achieve the challenging dual objectives of potency and selectivity to overcome the key obstacle: non-specific cytotoxicity. These problems are especially challenging for solid tumor therapy, where antigen tissue specificity, accessibility, and tumor microenvironment are problematic. Cells engineered with receptors that act as synthetic logic gates promise to address the issue of tumor specificity by targeting antigen profiles rather than single antigens. Nevertheless, there are limits to the potency benefit that can be achieved at the level of the antigen-targeting receptors. One approach to enhance potency beyond the acute sensitivity of receptor activation is to co-opt a major source of ancillary stimulation in the normal immune response, cytokine receptors.Methods Enhancing CAR-T efficacy with engineered onboard cytokines, often referred to as “armoring”, is one such approach to boost potency. However, such constructs run the risk of overriding tumor selectivity and eroding the therapeutic window. Here we design and test onboard cytokine constructs that enhance potency and preserve selectivity of a synthetic NOT logic gate construct called Tmod, potentially addressing some of the major challenges in oncology in a single synthetic design.Results We focused especially on a module encoding membrane-tethered interleukin (IL)-12, a construct that significantly enhances Tmod antigen-dependent long-term proliferation and potency both in vitro and in vivo, without compromising the NOT gate selectivity. Notably, three substantially different in vivo models, including one that employs mouse surrogate antigens, were used to assess preclinical dose-dependent efficacy and safety. Together, these studies make a strong case for the robustness of the design.Conclusions We conclude that the mem-IL-12 module can be combined with multiple Tmod constructs to boost efficacy and persistence while preserving the on-tumor selectivity.